2003
DOI: 10.1002/sim.1381
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood‐based confidence intervals for a log‐normal mean

Abstract: To construct a confidence interval for the mean of a log-normal distribution in small samples, we propose likelihood-based approaches - the signed log-likelihood ratio and modified signed log-likelihood ratio methods. Extensive Monte Carlo simulation results show the advantages of the modified signed log-likelihood ratio method over the signed log-likelihood ratio method and other methods. In particular, the modified signed log-likelihood ratio method produces a confidence interval with a nearly exact coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 12 publications
0
21
0
1
Order By: Relevance
“…We compare the confidence interval based on Cox' method (Land, 1972), the parametric bootstrap method (Angus, 1994), the modified signed log-likelihood ratio method (Wu et al, 2003) and Bayesian credible intervals for the lognormal mean. Two real examples are illustrated, and these examples analyzed by Wu et al (2003).…”
Section: Real Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…We compare the confidence interval based on Cox' method (Land, 1972), the parametric bootstrap method (Angus, 1994), the modified signed log-likelihood ratio method (Wu et al, 2003) and Bayesian credible intervals for the lognormal mean. Two real examples are illustrated, and these examples analyzed by Wu et al (2003).…”
Section: Real Examplesmentioning
confidence: 99%
“…They showed that Cox's method and the parametric bootstrap method are better than the other methods by numerical studies. Wu et al (2003) revealed that Cox's method does not appropriate when the sample size is small, and the parametric bootstrap has good coverage in small variance cases, but has not good performance for large variance cases. However the modified signed log-likelihood ratio method of Wu et al (2003) gives a good coverage even if the variance increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We will demonstrate that the proposed approach consistently outperforms the three approaches proposed by Zhou and Tu (2000). The adjusted signed log-likelihood ratio statistics have been widely used in interval estimation and it has been shown that this approach produces confidence intervals with nearly exact coverage probabilities and highly accurate and symmetric error probabilities even at very small sample sizes by many authors; for example, see for its application in the confidence interval estimation of the ratio of two independent lognormal means; see Wong and Wu (2002) for its application in confidence interval estimation of coefficient of variation; see Wu, Wong and Jiang (2003) for its application in confidence interval estimation of log-normal means; see Tian and Wilding (2005) for its application in construction of a confidence interval of the ratio of two inverse Gaussian means.…”
Section: Introductionmentioning
confidence: 99%
“…In this case it is clear that the coverage probability of the Z interval will be below the nominal level since t a=2; ðnÀpÞ > z a=2 . Wu et al (2003) specialized the results of Barndorff-Nielsen (1986 and Barndorff-Nielsen and Cox (1994) to obtain the modified signed likelihood ratio…”
Section: Introductionmentioning
confidence: 99%